WHY STAY? SAUDI WOMEN’S ADAPTIONS TO VIOLENCE - Alazab, Seham (PEOPLE: International Journal of Social Sciences, 2024)
The study investigates the reasons why women continue to live with an abusive husband and examines the relationship between their reasons and a number of variables that support one’s ability to cope with spousal violence. These variables include employment status, educational level, number of children, marriage duration, the social status of the wife's family and the number of violent incidents. A demographic survey and a spousal violence adaption scale were administered to a sample of 114 abused wives. The results revealed that all of the variables and several of the dimensions represented by the violence adaption scale affected the women’s decisions. The impact of these variables was more obvious among nonworking wives and the lesser educated, women with a greater number of children, those who had been married longer, those who senatal families had a low social status, and those who were subjected to violence more frequently. Keywords: adaptation to violence, marital violence, Saudi Arabia, spousal violence, violence against women in Saudi Arabia, why women stay in violent relationships.